Comparison Analysis of Financial Performance and Financial Distress before and during the Covid-19 Pandemic - Irma Citarayani; Melani Quintania; Arini Dwi Apriani (Sultan Publisher, 2024)
The purpose study was to analyze a comparison of financial performance and financial distress before and during the Covid-19 pandemic in the Hotel, Restaurant, and Tourism sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. In this study, a comparative descriptive method was used with a quantitative approach to test the impact of Covid-19 on financial performance and financial distress. The final sample of this study was 19 companies based on the elimination of the criteria that were only needed in this study. The proxies used to measure financial performance are profitability ratios (ROA, ROE, and NPM), while financial distress uses the Altman Z-Score model. Furthermore, these ratios were tested with a different test using the Wilcoxon sign rank test. The results showed that there were significant differences in the ratios of financial performance which included ROA, ROE, and NPM. Meanwhile, financial distress (Z-Score) also experienced significant differences between before and during the Covid-19 pandemic.